Novel class of photochromic molecules exhibiting photo-switching in the solid state - Loan, Thomas; Santra, Mithun; Bradley, Mark (Frontiers in Chemistry, 2023)
Photo-switching compounds have seen wide applications, including as super-resolution imaging agents, anti-counterfeiting dyes, and molecules able to control drug-receptor interactions. Whilst the number of these reported molecules has expanded in recent years, research has largely focused on derivatising existing classes of compounds, such as azobenzenes, spiropyrans, and diarylethenes. Here a new class of compounds, phenylindole alkene dimers, are presented as a novel class of photochromic molecules that exhibit photo-switching in the solid state. The synthesis of a small library of these compounds allowed their optical properties to be tuned. Surfaces coated with these photo-switches could find applications as writable materials in a variety of applications.